Urban-rural migration and congestion costs revisited: is there a triple dividend for cities in developing countries? - Torben Alexander Klarl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Many cities in developing countries suffer from bad health and environmental conditions due to urbanization. The paper shows that increasing urban manufacturing congestion costs do not necessarily imply a reduction of a city's health as well as of environmental quality as one could expect ex-ante. The model distills a range of the urban manufacturing sector size which generates a triple dividend: a situation in which the government can simultaneously improve health, reduce pollution, and increase the productivity of labour by investing in either green capital or urban infrastructure that reduces congestion costs.
Keywords: R13; R23; Q52; 330